2020
DOI: 10.1111/gcb.15362
|View full text |Cite
|
Sign up to set email alerts
|

Key rules of life and the fading cryosphere: Impacts in alpine lakes and streams

Abstract: Alpine regions are changing rapidly due to loss of snow and ice in response to ongoing climate change. While studies have documented ecological responses in alpine | 6645 ELSER Et aL. We propose four rules of life necessary for obtaining a fundamental and thus predictive understanding of how aquatic biota and ecosystems in alpine environments will respond to a changing cryosphere under ongoing climate change. Key rule 1: Temperature. Temperature has a fundamental effect on nearly all biological activities due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 116 publications
3
40
1
Order By: Relevance
“…Because microorganisms allocate resources to substrate acquisition depending on substrate availability, pairwise comparisons of EEA can indirectly inform us on substrate limitation. Comparing total C (AG + BG) versus N (LAP + NAG) and P (AP) acquiring EEA showed that generally more microbial effort is directed toward the acquisition of N and P as compared to C, indicating that communities were generally nutrient limited, with the majority of the GFSs being N-limited ( Figures 3A-D), which agrees well with past predictions for GFS microbial communities (Ren et al, 2019;Elser et al, 2020). High rates of weathering are hypothesized to take place beneath glaciers, which has the potential to liberate large quantities of P. However, much of this P is sediment-bound (Hawkings et al, 2016), and only a minority is thought to be bioavailable (only ∼1% by one estimate, Hodson et al, 2004).…”
Section: Biomass and Extracellular Enzyme Activity Across The Environsupporting
confidence: 88%
See 2 more Smart Citations
“…Because microorganisms allocate resources to substrate acquisition depending on substrate availability, pairwise comparisons of EEA can indirectly inform us on substrate limitation. Comparing total C (AG + BG) versus N (LAP + NAG) and P (AP) acquiring EEA showed that generally more microbial effort is directed toward the acquisition of N and P as compared to C, indicating that communities were generally nutrient limited, with the majority of the GFSs being N-limited ( Figures 3A-D), which agrees well with past predictions for GFS microbial communities (Ren et al, 2019;Elser et al, 2020). High rates of weathering are hypothesized to take place beneath glaciers, which has the potential to liberate large quantities of P. However, much of this P is sediment-bound (Hawkings et al, 2016), and only a minority is thought to be bioavailable (only ∼1% by one estimate, Hodson et al, 2004).…”
Section: Biomass and Extracellular Enzyme Activity Across The Environsupporting
confidence: 88%
“…In addition to sediments and water, GFSs also deliver DOC (e.g., Hood et al, 2009Hood et al, , 2015Singer et al, 2012), nitrogen (N) (Hodson et al, 2005;Wadham et al, 2016;Colombo et al, 2019), and phosphorus (P) (Hodson et al, 2004;Föllmi et al, 2009;Hawkings et al, 2016) to downstream ecosystems-all of them typically at low concentrations. However, concentrations of P generally increase with greater glacier influence in comparison to N, probably due to elevated rates of rock comminution beneath the glacier and dust deposition on glacier surfaces (Elser et al, 2020). Therefore, N limitation is predicted to be common for microbial life in GFSs (Ren et al, 2019;Elser et al, 2020), yet few studies have directly assessed nutrient limitation on the microbial life of GFSs (e.g., Robinson et al, 2002;Kohler et al, 2016), representing a considerable barrier in our understanding of the ecology of these habitat types.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The surfaces of CRLs are typically boulder‐strewn and heterogeneous, and include dry, rocky ridges, sediment‐filled depressions and unstable, shifting margins (Figure 2). Paired with the environmental challenges that already stem from high‐elevation habitat in mountain ecosystems (e.g., extreme cold, intense solar radiation, reduced oxygen availability; Birrell et al, 2020; Elser et al, 2020), instability of CRL mantles, routine avalanches, and rockfall make their surfaces particularly harsh environments. For temperature, cold is not the only risk.…”
Section: Cold Habitats For Biodiversitymentioning
confidence: 99%
“…We build on related reviews (e.g., Elser et al, in press; Hotaling et al., 2017; Jacobsen & Dangles, 2017; McGregor et al., 1995; Milner & Petts, 1994; Ward, 1994) by synthesizing the physiological challenges beyond temperature extremes that insects face in high elevation streams, from both singular and interactive perspectives. We explore the knowledge gaps identified above by first describing the physical and physiological challenges of life in high‐elevation streams and how they are being altered by climate change.…”
Section: Introductionmentioning
confidence: 99%